Definição lexicográfica em dicionários escolares do tipo 3 e 4 do PNLD: um estudo metalexicográfico - Ludymilla Tessari Dutra Rodrigues (2023)
This work, supported by the theoretical and methodological principles of Pedagogical Lexicography (LEXPED), in particular, the contributions of Biderman (1991), Almeida and Gomes (2012), Krieger (2006), Pontes (2009), among others, presents a study metalexicography on the semantic aspect of the microstructure of the entry. With this study, we investigated the definitions in PNLD school dictionaries, which are considered by authors such as Seco (1978) and Lara (1989) to be one of the central aspects among lexicographical studies. The main objective was to verify whether the definitions of lexical units recorded in four pedagogical dictionaries can meet the querent's understanding needs. The specific objectives established were: i) to discuss the types of definition in light of the principles of Lexicography; ii) reflect on the lexicographical definitions from the LEXPED, as a way of highlighting its characteristics and functionalities, according to the students' level of communicative competence; iii) assess whether the definitions recorded in dictionaries used in basic education are able to provide students with a clear understanding of the meaning of the addressed motto; iv) verify whether there is a difference in relation to the type of definition and the record used, considering type 3 dictionaries – proposed for students from 6th to 9th grade, and type 4 – intended for high school students. To this end, the definitions of lexical words from the semantic field dealing with cattle in Evanildo Bechara's dictionaries type 3 and 4 and in Caldas Aulete's dictionaries type 3 and 4 are examined, in order to investigate whether elementary and high school students can identify a motto, enjoying only its definition. The lexias analyzed were extracted from monolingual school dictionaries distributed by the PNLD, which, due to their didactic characteristic and the intention of their authors who conceived them as learning aids, motivated us to verify whether these works meet the needs of school students. basic and medium. This dissertation intends to contribute with the lexicographical organization for schoolworks. Keywords: Pedagogical Lexicography, definitions, PNLD.